EMPOWERING STUDENTS’ WRITING SKILL AND CREATIVITY THROUGH IMPLEMENTING GENRE-BASED APPROACH - Dadang Romawi; Andang Saehu; Hanna Sundari (Indonesian EFL Journal, 2024)
This study focused on investigating the ways the English teacher implemented a Genre-Based Approach to improving students’ writing skills and creativities. The case study was conducted in MAN 1 Cianjur. The respondents were 36 students and an English teacher. There were six students chosen to be interviewed in this study. The instruments of data collection were carried out by observing the teaching-learning process of the Genre-Based Approach and interviewing the students relating with their creativity. The result of the observation showed that the EFL teacher implemented the Genre-Based Approach properly. It was proved that the teacher implemented the steps well, and the students’ average scores improved from 70 to 90. Based on the interview, the Genre-Based Approach could help students to be creative by fulfilling fluency including producing great idea, providing solution or feedback, and having option to respond. Besides that, it could help them to fulfill the flexibility including producing various ideas and answers, looking for different alternatives, and changing perspectives. Moreover. It could help them to make an original text including producing new and unique expressions, thinking novel and unusual ideas, and combining unusual ideas. Furthermore, I could motivate them to elaborate on the text well including developing ideas and providing details and clarity by stating the end of the story, impression, and conclusion in the last paragraph of recount text.Keywords: Genre Based Approach; Creativity; Writing skill.